Characterization of the oral and gut microbiome in children with obesity aged 3 to 5 years - Ma, Ting; Wu, Zeyu; Lin, Jing; Shan, Chao; Abasijiang, Aisaiti; Zhao, Jin (Frontiers in Cellular and Infection Microbiology, 2023)
The ever-increasing global prevalence of obesity has trended towards a younger age. The ecological characteristics and changes of the oral and gut microbial community during childhood are poorly understood.In this study, we analyzed the salivary and fecal microbiota of 30 children with obesity and 30 normal weight children aged 3-5 years via third-generation long-range DNA sequencing,with the aim of understanding the structure of childhood microbiota and identifying specific oral and gut microbial lineages and genera in children that may be associated with obesity.The results revealed significant variation in alpha diversity indices among the four groups (Chao1: P < 0.001; observed species: P < 0.001; Shannon < 0.001). Principal coordinate analysis (PCoA) and nonmetric multidimensional scaling (NMDS) revealed significant differences in oral and gut microbial community structure between obesity and controls. The Firmicutes/Bacteroidetes (F/B) abundance ratios of oral and intestinal flora among children with obesity were higher than those of controls. The most abundant phyla and genera found in oral and intestinal flora were Firmicutes, Proteobacteria, Bacteroidetes, Neisseria, Bacteroides, Faecalibacterium, Streptococcus, Prevotella and so on. Linear discriminant analysis effect size (LEfSe) revealed higher proportions of Filifactor (LDA= 3.98; P < 0.05) and Butyrivibrio (LDA = 2.54; P < 0.001) in the oral microbiota of children with obesity, while the fecal microbiota of children with obesity were more enriched with Faecalibacterium (LDA = 5.02; P < 0.001), Tyzzerella (LDA=3.25; P < 0.01), Klebsiella (LDA = 4.31; P < 0.05),which could be considered as dominant bacterial biomarkers for obesity groups.A total of 148 functional bacterial pathways were found to significantly differ in the oral and gut microbiota among controls and obesity using PICRUSt 2. Most predicted functional pathways were clustered in biosynthesis. In conclusion, This work suggests there were significant differences in oral and gut microbiota in controls and obesity groups, microbiota dysbiosis in childhood might have significant effect on the development of obesity.